Mass Transfer in Hierarchical Silica Monoliths Loaded With Pt in the Continuous-Flow Liquid-Phase Hydrogenation of p-Nitrophenol - Jatoi, Haseeb Ullah Khan; Goepel, Michael; Poppitz, David; Kohns, Richard; Enke, Dirk; Hartmann, Martin; Gläser, Roger (Frontiers in Chemical Engineering, 2021)
Sol-gel based silica monoliths with hierarchical meso-/macropores are promising catalyst supports and flow reactors. Here, we report the successful preparation of cylindrically-shaped Pt-loaded silica monoliths (length: 2 cm, diameter: 0.5 cm) with a variable mean macropore width of1, 6, 10 or 27 µm at a fixed mean mesopore width of 17 nm. The Pt-loaded monolithic catalysts were housed in a robust cladding made of borosilicate glass for use as flow reactor. The monolithic reactors exhibit a permeability as high as 2 µm2 with a pressure drop below 9 bar over a flow rate range of 2 – 20 cm3 min-1 (solvent: water). The aqueous-phase hydrogenation of p-nitrophenol to p-aminophenol with NaBH4 as a reducing agent was used as a test reaction to study the influence of mass-transfer on catalytic activity in continuous flow. No influence of flow rate on conversion at a fixed contact time of 2.6 s was observed for monolithic catalysts with mean macropore widths of 1 or 27 µm. As opposed to earlier studies conducted at much lower flow velocities, this strongly indicates the absence of external mass-transfer limitations or stagnant layer formation in the macropores of the monolithic catalysts.